CXCR1- or CXCR2-modified CAR T cells co-opt IL-8 for maximal antitumor efficacy in solid tumors - Linchun Jin (Nature Portfolio, 2019)
CAR T-cell therapy efficacy in solid tumors is limited by inadequate T-cell migration and/or persistence in tumour microenvironment. Here, the authors show that the activity of tumour-antigen specific CAR T cells, in multiple preclinical mouse models, can be enhanced by co-expression of two IL-8 receptors that mediate their migration into the tumor microenvironment when IL-8 production in tumor is naturally expressed or enhanced by radiation.